Facile synthesis, structural and luminescence studies of MgTiO3:Sm3+ nanophosphor for display applications - Thammanna, B.M.; Kumar, Dr. V. Senthil (International Journal of Engineering and Technology, 2026)
Luminescence properties of combustion prepared Mg2TiO3:Sm3+ (1-11 mol %) phosphors were studied in the present work. The crystallite size (D) was in the range20- 40 nm as estimated and it was similar to Transmission electron microscopy (TEM) results. The band gap of the materials was in the range 4.45 to 4.87 eV as calculated using Kubelka-Monk function. The PL peaks of Sm3+ ions are due to the intra 4-f orbital transitions (4G5/2à6H5/2, 4G5/2à6H7/2, 4G5/2à6H9/2 and 4G5/2à6H11/2). Among the samples, 5 mol % doped one shows the highest PL intensity under 413 nm excitation. The CIE chromaticity coordinates showed orange of red emission (CCT ~2036 K), as a result Mg2TiO3:Sm3+ (1-11 mol %) Nanophosphors were obviously for solid-state lighting and warm white light emissive display applications.